Classification of the Contract; Tabarru Lending Money, Qardh, Rahn, Hiwalah - Yudi Khoeri Abdillah; Agung Wildan Azizi; Ahmad Yusdi Gozaly; Akfah Zakiah Jamilah (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2023)
Tabarru 'Lending Money, Qardh, Rahn, Hiwalah Islamic financial institutions in practice have two categories of contracts, there are so-called Tijarah contracts and Tabarru' contracts. expect rewards, which include tabarru' contracts including qardh, Rahn, Hiwalah contracts, in this scientific paper will explain the concept of pillars, terms, types, and Tabarru' contract practices in Islamic financial institutions. The methodology in this scientific paper uses a qualitative descriptive methodology which describes the classification of the contract; tabarru' lending money, qardh, rahn, hiwalah.Tabarru' Lending Money, Qardh, Rahn, Hiwalah, it can be concluded that from each tabarru contract such as qardh in its transaction activities, additional transactions are not allowed, if there is an additional qardh contract from each loan then the status of the law is usury. Likewise with rahn or sharia pawning does not apply interest from each rahn contract, but in a rahn or sharia pawn contract there is a maintenance fee for goods used as collateral or collateral. As for the hawalah contract, it is permissible to do ad-Dain (assets that are still in the form of debt), not to alAin (assets whose goods are concrete, usually interpreted as goods), or in other words, the hawalah contract is valid if the muhal bih is not in the form of goods debt (alAin).